IKON HABIBIE-AINUN, STRATEGI INOVATIF DALAM MENGEMBANGKAN PARIWISATA DI KOTA PAREPARE, SULAWESI SELATAN - Ilham Junaid; Hamsu Hanafi (Magister Tourism Study, Faculty of Tourism, Udayana University, 2016)
Empirical data on how the local governments implement tourism innovation is very limited. Thus, it is necessary to explore how the regional board of tourism develops tourism potential through innovative approach.The aims of this research are to explore the festival of Habibie-Ainun as well as to recommend ways in optimizing the festival for community welfare.This research is a qualitative study by interviewing (in-depth interview) four staff at the regional board of tourism as well as doing participant observation at Parepare city.The research reveals that Habibie-Ainun is choosen as an icon of tourism because of the enchantment of Habibie, the former president of Indonesia who was born in Parepare city.Habibie-Ainun festival, becak of tourism and the statue of Habibie-Ainun are considered as innovative strategies in attracting tourists.This research suggests that strategy of Habibie-Ainun should be supported with various and continuous activities that may involve tourists particularly in the area of the statue.The local government should also inform the community on how the strategy can help community improve their income through tourism. Innovative strategies may come from the community, and thus, it is important to strengthen synergy between the local government and the community.